Geographical Dimension of Colonial Justice: Using GIS in Research on Law and History. (8th September 2016) - Ng, Michael; Chow, T. Edwin; Wong, David W.S.
Abstract : This article reviews and reflects on the use of the geographic information system (GIS) as a tool, or geographic information science (GIScience) as a research methodology, and associated techniques of analysis in an empirical study-in-progress on the law and history of early twentieth century British Hong Kong. The article begins by introducing the study and its objectives, as well as the rationale for adopting GIS/GIScience as one of its research methodologies. It then highlights the preliminary findings of the current project and compares them with those of earlier research on the legal history of early twentieth century Beijing using GIS. The article also discusses the difficulties involved in adopting such a digital tool and methodology in historical research. It concludes by reflecting on what GIS can help scholars understand about the social history of law in Hong Kong, beyond what is already known, and how specialists in law, history, and geography can collaborate in a digital law and history project involving the use of GIS. This article also gives an overview of the use of GIS in conducting empirical research in the humanities (including but not limited to history and legal history research) and points to digital sources and web sites useful to researchers who may need tools and data to launch a GIS study in law and history.